Statutes of the State of Rhode Island Relating to the City of Providence 432 (1875) - (:unkn) unknown (My University, 1874)
Ch. 5, § 105: He may also arrest without a warrant any person reasonably suspected of having committed a felony, or seen committing a breach of the peace, or being unduly armed with a dangerous weapon, and also night-walkers.
Keywords: CARRY - DANGEROUS PERSONS